Mitigating organizational risks in the Secretariat of the Finance Education and Training Agency: A House of Risk methodology - Anggraeni, Shanti Kirana; Wahyuni, Nuraida; Soleha, Iim Imroatu; Katili, Putiri Bhuana; Ulfah, Maria (Journal Industrial Servicess, 2024)
One regulation of the Head of the Financial Education and Training Agency (BPPK) states that the BPPK Secretariat is an Echelon II Unit within BPPK, tasked with coordinating duties, coaching, and providing administrative support to all BPPK elements. In its management process, the BPPK Secretariat encounters various opportunities and risks. This study aims to identify and manage organizational risks at the BPPK Secretariat. The House of Risk (HOR) method's Phase 1 is used for risk identification, analysis, and evaluation, while Phase 2 is used for risk mitigation. Additionally, the Failure Mode and Effects Analysis (FMEA) method is used to assess severity and occurrence, and Pareto diagrams are used to determine priority risk sources. The study identified 22 risk events, 46 sources of risk, 5 priority risk sources, and proposed 9 mitigation actions. One identified risk event is the inadequate level of employee understanding of the learning organization, with the source of risk being the lack of optimal activities that can provide understanding to employees regarding the learning organization. This source of risk is a priority risk source, leading to proposed mitigation actions such as conducting socialization, dissemination, webinars, talk shows, and assistance activities about learning organizations.